Some Molecular Adducts of Telluracylopentane-1,1-diiodide - Srivastava, Shekhar (Asian Journal of Chemistry, 2010)
Some molecular adducts of telluracyclopentane-1,1-diiodide, (CH2)4TeI2 of the type (CH2)4 TeI2·L (where L = pyridine-N-oxide, 4-picoline-N-oxide, 2,6-lutidine-N-oxide, triphenylphosphine oxide and tetramethylene sulphoxide) have been prepared and characterised by elemental analysis, conductivity, IR and X-ray photoelectron spectral data.